Nuclear Factor κB Activation in a Type V Pityriasis Rubra Pilaris Patient Harboring Multiple CARD14 Variants - Danis, Judit; Göblös, Anikó; Gál, Brigitta; Sulák, Adrienn; Farkas, Katalin; Török, Dóra; Varga, Erika; Korom, Irma; Kemény, Lajos; Széll, Márta; Bata-Csörgö, Zsuzsanna; Nagy, Nikoletta (Frontiers in Immunology, 2018)
Pityriasis rubra pilaris (PRP) is a rare papulosquamous skin disorder, which is phenotypically related to psoriasis. Some familial PRP cases show autosomal dominant inheritance due to CARD14 mutations leading to increased nuclear factor κ B (NFκB) activation. Moreover, CARD14 polymorphisms have also been implicated in sporadic PRP. A Hungarian PRP patient with childhood onset disease showing worsening of the symptoms in adulthood with poor therapeutic response underwent genetic screening for the CARD14 gene, revealing four genetic variants (rs117918077, rs2066964, rs28674001, rs11652075). To confirm that the identified genetic variants would result in altered NFκB activity in the patient, functional studies were carried out. Immunofluorescent staining of the NFκB p65 subunit and NFκB–luciferase reporter assay demonstrated significantly increased NFκB activity in skin samples and keratinocytes from the PRP patient compared to healthy samples. Characterization of the cytokine profile of the keratinocytes and PBMCs demonstrated that the higher NFκB activation in PRP cells induces enhanced responses to inflammatory stimuli. These higher inflammatory reactions could not be explained solely by the observed CARD14 or other inflammation related gene variants (determined by Whole Exome Sequencing). Thus our study indicates the importance of investigations on other genetic factors related to PRP and their further functional characterization to bring us closer to the understanding of cellular and molecular background of disease pathogenesis.